ACCOUNTABILITY OF CONSTRUCTION SERVICES CONTRACT BY VILLAGE GOVERNMENT IN KARAWANG DISTRICT - Putra, Pamungkas Satya (Yustisia, 2014)
One of the principles in Law Number 2 of 2017 concerning Construction Services is the principle of mutually beneficial partnerships. With this principle, the linkages can be realized in an efficient and effective unity between service providers. Such a partnership also means providing greater business opportunities without ignoring the rules of efficiency and effectiveness and benefits. This is one of the efforts to accelerate the development of the Village Government. The research method uses normative juridical with descriptive analytical research specifications. Descriptive because the results of this study are expected to obtain a comprehensive and systematic description of the construction service agreement relating to the problems raised in this study. The results of the discussion are: Regulation in Law Number 2 of 2017 concerning Construction Services for legal renewal from the previous Law Number 18 of 1999 concerning Construction Services. The government should make adjustments to the implementing regulations of the law, including the Karawang Regency Regional Regulation related to the responsibility of the Village Government in the implementation of this Construction Service so that it complies with the provisions of Law Number 2 of 2017. Then the government is advised to impose other technical regulations considering that the legal problems of construction services that have the potential to criminalize are quite varied in Indonesia.